Pembatasan Penggunaan Surat Kuasa dalam Praktik Kenotariatan: Studi Perbandingan Indonesia dan Swedia - diah ayuning; nuzula kumala sari; Yusuf Adiwibowo (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the regulation of powers of attorney in notarial practice through a comparative study of law between Indonesia and Sweden, using normative juridical methods and comparative, statutory and conceptual approaches. The results reveal fundamental differences in the regulation of absolute powers of attorney. Indonesia imposes restrictions on absolute powers of attorney, particularly in the transfer of land rights, to maintain order in land administration and prevent legal smuggling. In contrast, Sweden, through its fullmakt regulation in Avtalslagen, provides greater flexibility by emphasizing third-party protection and transaction certainty. The study also found that Indonesian notaries bear broader responsibility for the formal and material correctness of deeds, while the Swedish Notarius Publicus focuses on identity verification and signature authenticity. These findings suggest the need to strengthen digital verification systems and reformulate notarial accountability regulations to increase legal certainty and prevent fraud.